Cyberneticisation as a Theory and Practice of Matter - Rolf Hughes; Rachel Armstrong (Footprint)
The ecological implementation of cybernetic ideas in architecture requires a material theory and practice that enables their propositions to be tested. The need for approaches that move from simulation to cybernetic reality is a documented limitation of cybernetics recognised by Stafford Beer with his pond ecology experiments and Gordon Pask through electrochemical devices. While both experimented with adaptive material platforms as embodiments of designed cybernetic systems, their approaches were limited by the available toolsets. This article considers an ecological trajectory of cybernetisation by revisiting notions of biological computation as a generative material practice. In particular, the growing fields of biodesign and living architecture go beyond notions of biological analogues that inform modern architecture by directly incorporating living systems into the very fabric of buildings as designed expressions of ecology.